PEMODELAN ARUS LALU LINTAS DAN WAKTU TUNGGU TOTAL OPTIMAL DI PERSIMPANGAN JL. JEMUR ANDAYANI AHMAD YANI SEBAGAI UPAYA MENGURAI KEMACETAN - Farida, Yuniar; Fanani, Aris; Purwanti, Ida; Wulandari, Luluk; Zaen, Nanida Jenahara (PATTIMURA UNIVERSITY, 2020)
One crossroad of ​​Surabaya whose high level of congestion is the crossing of Jemur Andayani – Ahmad Yani Street. It needs to Improve traffic management, geometric, and signal time to obtain optimal traffic performance. The purpose of this study is to make a model of traffic flow and determine the optimal total waiting time at the crossing of Jemur Andayani – Ahmad Yani using Compatible Graph. Compatible graphs are two sets where vertices indicate objects to be arranged and edges indicate compatible pairs of objects. Compatible traffic flow is two traffic flows which if both of them run simultaneously can run safely and not collide. The results of the optimal waiting time calculation using a compatible graph assuming the left turn following the lamp is 75 seconds. While the optimal total waiting time by assuming the left turn not following the lights is 60 seconds. The optimal total waiting time is smaller than the actual total waiting time currently applied at Frontage Ahmad Yani street, which is 170 seconds by assuming turn left following the lights.